Répondre :
Il n'y a qu'a remarquer que (x+1)/x = 1 => x+1 = x² => =x² - x - 1 0 (si x pas éfgal à 0)
x² - x + 1/4 - 5/4 = 0 => (x - 1/2)² = 5/4 => x - 1/2 = V5//2 ou x - 1/2 = -V5/2= (1-V5)/2
x = 1/2 + V5/2 ou x = 1/2 + V5/2 = fi
fi² = (1/2 + V5/2)² = (6 + 2V5)/4 = (3 + V5)/2
1 + fi = 1/2 + V5/2+2/2 = (3+V5)/2
1/fi = 2/(1+V5) = 2(1-V5)/(1-5) = (1-V5)/-2= (V5 - 1)/2
fi - 1 = 1/2 + V5/2 - 1 = V5/2 - 1/2 = (V5 - 1)/2
si on reprend l'équation x² - x - 1= 0
fi + fi' = 1/2 ; fi.fi' = -1 ; fi² + fi'² = (fi + fi')² - 2fifi' = 1/4 + 2 = 9/4